Lesson Study… and its effects - Buchard, Julien; Martin, Daniel (Έρευνα στην Εκπαίδευση, 2017)
The aim of this contribution is to draw up a theoretical framework to evaluate Lesson Studies (LS) embedded in the schooling context in Lausanne, in the French-speaking part of Switzerland. Firstly, we provide a (re)definition of LSs through a comprehensive literature review. Some reference works like the books of Lewis & Hurd (2011) or Fernandez & Yoshida (2004) enable their readers to build a clear comprehension of what LSs are and how they should be implemented. But the LS practices reported in scientific journals show some variation compared with the theoretical model. To evaluate such a process, we postulate that one has to clearly define what is supposed to be measured and identify its limits. Secondly, we present a synthesis of the different ways to measure the effects of LS as reported in the literature. This second focus leads us to list and discuss the features and components of LS which could (or should) be evaluated and the data to be collected to do so. At the same time, our work highlights some differences between LS practices depending on the variation of several parameters. These two topics lead us to question the effects expected from each feature and component of an LS. Some elements are not on the existing list of essential features of an LS. Others, experimented in groups of teachers, are not even mentioned in the reference literature. Yet they can be keys to breaking a stalemate, to overcoming a barrier or simply helping organise the research of a LS group according to their goals. In March 2017, we submitted this presentation and a database of such keys and their expected results for discussion in the Scientific symposium organised by the Post-graduate Studies Program of the Department of Education Sciences in Early Childhood “Innovative educational approaches in multi-cultural educational environments” (Democritus University of Thrace) and the Municipality of Alexandroupolis (GR). This article reports the main ideas of this presentation.